A mixed method study of flex nurses' work-related social relationships - MacPhee, Maura Stilson, author; Morgan, George A., advisor (Colorado State University. Libraries, 1999)
The health care industry has undergone radical changes during the past ten years. To remain competitive, many hospitals have adopted nurse staffing models that accommodate patient census variability. One model, the Flex nursing model, is comprised of nurses who work without benefits and can be cancelled if not needed. In turn, the nurses design their own work schedules. Little is known about individuals who choose flexible work arrangements. According to American business predictions, however, "flexible workers" are desired in times of change, and flexible work models are expected to increase in the future. The purpose of this dissertation was to study the nature of social relationships at work for nurses within a Flex nursing model. The socialization process and its outcomes, social supports, are considered critical to the formation of job satisfaction, work commitment, and job retention. If flexible workers are going to be an important component of the organizational workforce, it is necessary to understand how these individuals meet their social needs at work. A mixed method case study employed a standardized assessment tool, The Social Network Questionnaire, to contrast differences in social network composition and emotional and instrumental support needs between Flex nurses and Regular nurses. The qualitative component of the study consisted of Flex nurse interviews and observations of Flex nurses interacting with their co-workers. There were no significant differences in overall network composition between Flex and Regular nurses. There were differences in the utilization of peers for different kinds of emotional supports. The qualitative portion of the study revealed four major themes for Flex nurses. These themes were: flexibility, safety, support, and commitment. Triangulation between the qualitative and quantitative findings, and between the study's outcomes and the nursing and organizational psychology literature, identified some important training and development considerations for individuals who comprise flexible work systems.
Keywords: nursing; public health